Energy Efficiency for Biodiesel Production by Combining Two Orifices in Hydrodynamic Cavitation Reactor - Mahlinda Mahlinda; Fitriana Djafar (Biopropal Industri, 2014)
Research of energy efficiency for biodiesel production process by combining two orifices on  hydrodynamic cavitation reactor had been carried out. The aim of this reseach was to studied effect of the number of orifices toward increasing temperature without using external energy source to produce biodiesel that generated by cavitation effects on orifices. The results of preliminary research showed by combining two orifices arranged in series can produce the highest thermal energy reached 48oC. Result of biodiesel production showed that yield of the highest biodiesel was 96.34% using molar ratio a methanol:oil with comparison 6:1, KOH as catalyst (1%) for 50 minutes processing time. For biodiesel quality testing showed all selected parameter met the requirements of the Indonesian National Standard (SNI) 04-7182:2006. Identification of biodiesel compound using GCMS showed the biodiesel compounds consisted of methyl oleate, methyl palmitate, acid linoleid, methyl stearate, palmitic acid and oleic acid with the total contents 98.39%.